Gibberellin and potassium sorbate synergy for parthenocarpy and sugar enhancement in Bali grapes, Indonesia - RINI HERMINA KAMUHI; RINDANG DWIYANI; IDA AYU PUTRI DARMAWATI (Smujo International, 2025)
Abstract. Kamuhi RH, Dwiyani R, Darmawati IAP. 2025. Gibberellin and potassium sorbate synergy for parthenocarpy and sugar enhancement in Bali grapes, Indonesia. Asian J Agric 9: 568-581. Bali grape (Vitis vinifera L. var. Alphonso Lavallee) is a high-value horticultural commodity; however, its fruit quality, particularly sweetness and seed content, often falls short of consumer expectations. This study aimed to evaluate the effects of gibberellin (GA3) and potassium sorbate applications on parthenocarpy induction and sugar content enhancement. The experiment employed a factorial randomized complete block design with two factors: GA3 concentrations (0, 50, 100, and 150 ppm) and potassium sorbate concentrations (0 and 0.3%), each with five replications, resulting in 40 experimental units. Results showed that both GA3 and potassium sorbate significantly affected cluster and fruit characteristics, including cluster length, pedicel length, fruit number and weight, as well as seed number and weight. The interaction between the two treatments had a significant effect on berry diameter, number of millerandage (undeveloped) berries, and sugar content. The combined application of 150 ppm GA3 and 0.3% potassium sorbate increased berry diameter to approximately 19 mm and sugar content by about 38% to 19°Brix, while reducing the number of millerandage berries to 1.60 per cluster. GA3 at 150 ppm effectively reduced seed number and seed weight, while increasing fruit number, fruit weight, cluster weight, and cluster size. Potassium sorbate also contributed to improving the physical quality of the fruit. These findings indicate a synergistic effect between GA3 and potassium sorbate. The combined application, which is both practical and cost-effective, offers a promising agronomic strategy to improve the fruit quality of Bali grape, thereby enhancing its competitiveness in both domestic and international.